On The Value Implied In The Data Referred To In The Mahābhārata for π - Dipak Jadhav (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2018)
E. Washburn Hopkins interpreted, in 1902, the values for  from the data referred to in some verses contained in the Bhīṣma Parva of the Mahābhārata where  is a non-terminating and non-recurring fixed ratio of the circumference, , of a circle to its diameter, . The values interpreted for it by him from the data referred to for the dimensions, including , , and vipulatva , of the Rāhu, the Moon, and the Sun are 3.5, 3.5+, and 3.58 respectively. R. C. Gupta found, in 1990, these values to be the yielding of the gross misinterpretations. He pointed out that the value implied in the data of each of the three cases is only 3. The present paper is mainly aimed at probing when and why 3 was used in the Mahābhārata as the value for . The date when those above verses were incorporated in the Mahābhārata is the one when 3 as the value for  was used in the same if consistency is preferred to as a sound criterion in determining so. It tends to 500 BCE in its range extending from 500 BCE to 500 CE. It may go even beyond 500 BCE. 3 as the value for  seems to have been borrowed from some older forms of the Purāṇas into the Mahābhārata. If simplicity, prevalence, and traditionalism are preferred to as a sound criterion to calculate for a given , no other option for  is better than 3. The support for this option was available not only in the interior of India right from the Ṛgveda but also in the exterior of India at least right from the old Babylonian text.